The relationship between the use of digital display devices and headphones and primary headaches in children - Çaksen, Hüseyin; Özçelik, Nadire Ş; Güven, Ahmet S; Kılıç, Ahmet O (Boletin medico del Hospital Infantil de Mexico, 2023)
Headache represents the most common neurologic symptom in children. In this study, we investigated the relationship between watching television, listening to music with headphones, smartphone, tablet, and computer use, and primary headaches in children. We aimed to determine whether primary headache in children is associated with excessive use of digital display devices and headphones and whether reducing the use of digital display devices and headphones affects primary headache. The study included 69 children with primary headaches and 64 with no headaches as a control group. All subjects were evaluated for demographic and headache characteristics and the use of digital display devices and headphones. Our recommendation for patients and families was to decrease the use of digital display devices and headphones, and the headache burden was re-evaluated after one month. Headache frequency was more common in patients who watched television and used smartphones or tablets for more than 6 hours per day. Using a smartphone or tablet for more than 3 hours daily was more common in the study group than the control group. Headache frequency decreased in all patients one month after the digital imaging device and headphones were restricted. Watching television and using a smartphone or tablet strongly associates with primary headaches during childhood.